Neutrophil-derived Activin-A moderates their pro-NETotic activity and attenuates collateral tissue damage caused by Influenza A virus infection - Divolis, Georgios; Synolaki, Evgenia; Doulou, Athanasia; Gavriil, Ariana; Giannouli, Christina C.; Apostolidou, Anastasia; Foster, Martyn L.; Matzuk, Martin M.; Skendros, Panagiotis; Galani, Ioanna-Evdokia; Sideras, Paschalis (Frontiers in Immunology, 2024)
Pre-neutrophils, while developing in the bone marrow, transcribe the Inhba gene and synthesize Activin-A protein which they store and release at the earliest stage of their activation in the periphery. However, the role of neutrophil-derived Activin-A is not completely understood. To address this issue, we have developed a neutrophil-specific Activin-A-deficient animal model (S100a8-Cre/Inhba fl/fl mice) and analyzed the immune response to Influenza A virus (IAV) infection.We found that neutrophil-specific Activin-A deficiency led to exacerbated pulmonary inflammation and widespread hemorrhagic histopathology in the lungs of IAV-infected animals that was associated with exuberant production of neutrophil extracellular traps (NETs). Moreover, deletion of the Activin-A receptor ALK4/ACVR1B in neutrophils exacerbated IAV-induced pathology as well, suggesting that neutrophils themselves are potential targets of Activin-A-mediated signaling. The pro-NETotic tendency of Activin-A-deficient neutrophils was further verified in the context of thioglycollateinduced peritonitis, a model characterized by robust peritoneal neutrophilia. Of importance, transcriptome analysis of Activin-A-deficient neutrophils demonstrated alterations consistent with a predisposal for NET release.Collectively, our data demonstrate that Activin-A, secreted by neutrophils upon their activation in the periphery, acts as a feedback mechanism to moderate their pro-NETotic tendency and limit the collateral tissue damage caused by neutrophil excess activation during the inflammatory response.